Tumor Immune Microenvironments (TIMEs): Responsive Nanoplatforms for Antitumor Immunotherapy - Sui, Xueqing; Jin, Teng; Liu, Tonghui; Wu, Shiman; Wu, Yue; Tang, Zhongmin; Ren, Yan; Ni, Dalong; Yao, Zhenwei; Zhang, Hua (Frontiers in Chemistry, 2020)
Interest in cancer immunotherapy has rapidly risen since it offers many advantages over traditional approaches, such as high efficiency and prevention of metastasis. Efforts have primarily focused on two major strategies for regulating the body’s antitumor immune response mechanisms: “enhanced immunotherapy” that aims to amplify the immune activation, and “normalized immuno” that corrects the defective immune mechanism in the tumor immune microenvironments (TIMEs), which returns to the normal immune trajectory. However, due to the complexity and heterogeneity of the TIMEs, and lack of visualization research on the immunotherapy process, cancer immunotherapy has not been widely used in clinical setting. Recently, through the design and modification of nanomaterials, intelligent TIME-responsive nanoplatforms were developed from which encouraging results in many aspects of immunotherapy have been achieved. In this mini review, the status of designed nanomaterials for nanoplatform-based immune regulation of TIMEs has been emphasized, particularly with respect to the aforementioned approaches. It is envisaged that future prospects will focus on a combination of multiple immunotherapies for more efficient cancer inhibition and elimination.